Uterine smooth muscle tumors of uncertain malignant potential: a 13-year retrospective study - Liu, Liuliu; Xiao, Zhendong; Li, Zhiwen; Zheng, Jinyu (Frontiers in Oncology, 2024)
ObjectiveThe primary objective of this study was to provide valuable evidence for the management of patients diagnosed with uterine smooth muscle tumors of uncertain malignant potential (STUMP), with a focus on those with reproductive aspirations.MethodsWe conducted a retrospective analysis of clinical and pathological data from the medical records and slides of STUMP patients treated at Drum Tower Hospital, affiliated with Nanjing University Medical School, from January 2009 to December 2021.ResultsThirty-four patients were included in the study, with a median follow-up duration of 76 months (range: 13-157 months). After slide review, the diagnosis agreement rate was 77.3% (34/44 among initially considered cases). The consistency rate between our hospital’s diagnosis and those of other institutions was 75% (15/20). The accuracy rate of intraoperative frozen section diagnosis was low, at 21.4% (3/14). Half of the patients (17) underwent myomectomy, while the other half (17) received hysterectomy, including one subtotal hysterectomy. Two recurrences were observed (5.9%), one as STUMP and the other as leiomyosarcoma, with one recurrence in each surgical group. Notably, 4 of 9 patients with reproductive aspirations successfully underwent cesarean deliveries. Patients with single lesions appeared to exhibit potentially favorable fertility outcomes compared to those with multiple lesions.ConclusionThe diagnosis of STUMP was difficult. Myomectomy potentially could serve as an alternative for patients with reproductive needs. In selected cases with single lesions, it may indicate potentially favorable fertility outcomes.